A new analytical critical thrust force model for delamination analysis of laminated composites during drilling operation. (1st September 2017) - Ojo, Saheed Olalekan; Ismail, Sikiru Oluwarotimi; Paggi, Marco; Dhakal, Hom Nath
Abstract: Fibre reinforced polymer (FRP) composite laminates are employed in many industrial applications due to their attractive mechanical and structural properties. Machining operation, such as drilling of FRP laminates, plays a significant role in the assembly of parts in aircraft and spacecraft production. Among other production bottlenecks, drilling-induced delamination remains a major defect which adversely affects the quality of assembly parts. An efficient strategy in preventing this problem is the calculation of the critical thrust force above which delamination is initiated. Therefore, in this study, a new analytical model is proposed to predict the critical thrust force for delamination. Unlike the general models in the literature which derived only mode I strain energy release rate based on the assumption of classical laminate plate theory (CLPT) combined with linear elastic fracture mechanics (LEFM) mode I considerations in the elliptic delamination zone, the proposed analytical model is derived based on first-order shear deformation theory (FSDT) and accounts for mode I and mode II strain energy release rates in the delamination zone. This strategy allows to activate mixed mode criteria for delamination initiation which is a valid assumption for laminates with layers of different orientations. The present model is partly derived for general laminates subject to distributed loading and further extended to cross-ply laminate sequence subject to a mixed load condition. The results show that the effect of shear deformation in the prediction of the critical thrust force is influential with increasing ply thickness and the effect of chisel edge on shear deformation is more profound in the distributed load regime.